Peningkatan Kemampuan Membaca Siswa Menggunakan Media E-Book Kelas III A UPTD SDN 145 Inpres Pampangan - Abdan Syakur; Anjeli Aulya; Asmaul Husna Ali; Fajar Syamsi (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research aims to improve students' reading skills using E-Book media in class III A UPTD SDN 145 Inpres Pampangan. This research is Classroom Action Research, the subjects of this research are III A, totaling 33 students consisting of 16 men and 17 women. This research was carried out for 3 weeks. The implementation of this action was carried out for three weeks, each week including learning and assessment. The presentation of the first cycle material begins on 14 September 2023 and the first cycle test on 18 September 2023. The presentation of the second cycle material begins on 19 September 2023 and the second cycle test is carried out on 23 October 2023. The results of the research show that the learning interest of the first cycle students reaches the average -average 73.3%. Then in cycle II it increased to 88.5%. The contribution of implementing Wordwall learning media to increasing students' interest in learning is very significant, meaning it is in the high category. So it can be concluded that the teacher's ability to apply E-book media in learning has succeeded in improving the reading ability of class III A students at UPTD SDN 145 Inpres Pampangan.